Prevalence of sexually transmitted infections among men having sex with men of urban Vadodara - Panchal, Preeti P.; Shringarpure, Kalpita S; Damor, Jivraj R.; Mazumdar, Vihang S. (International Journal Of Community Medicine And Public Health, 2019)
Background: Men having sex with men (MSM) are at higher risk of getting STIs, including HIV. Their role as bridge population is also very important in the spread of HIV. This study was done with the objective to study the demographic and behavioural factors of MSM and to measure the prevalence of STI among MSM using laboratory facilities of regional RTI/STI centre. Methods: This was a cross sectional study conducted at a targeted intervention (TI) site of Vadodara city. Sixty-eight MSM were enrolled, counselled regarding HIV and other STI testing followed by an interview using a pretested semi-structured study instrument for the information regarding socio-demographic status, sexual behaviour, present and past history of STI and health seeking behaviour. Following that, clinical examination for presence of any signs of STI and sample collection [oro-pharyngeal, urethral and anorectal swab] was done in an examination room and blood samples were collected. The samples were tested for various STIs at Regional RTI/STI centre. Results: Thirty-seven percent of MSM were bisexual. 37% MSM were not using condom consistently with ‘unavailability at all the time’ being the main reason. Six out of 68 MSM found positive of STI. Prevalence was maximum for Chlamydia infection followed by HSV2, HBsAg. Conclusions: Prevalence of STI was 8.82% among MSM of Vadodara city.